Contributions of technological methods in improving the performance of employees in the Palestinian public sector by application to the Ministry of Social Development - Jenin Directorate - Yahya, Khaireya Radwan; Yahia, Bahaa Ahmmad (Journal of Economic, Administrative and Legal Sciences, 2023)
This study aimed to identify the technological technology. In order to achieve the goal, a questionnaire was designed and composed of (31) items, and its validity was established, and the reliability coefficient Crowe Nabach alpha was calculated, which amounted to (0.87). The questionnaire was distributed to a sample of (20) employees in the Ministry of Social Development - Jenin Directorate, and the questionnaires were processed by the (SPSS) program. the most important results showed that the degree of contribution of technological methods to improving the performance of the Palestinian government sector employees, by applying it to the Palestinian Ministry of Social Development - Jenin Directorate, was highly appreciated with a percentage of (74.09%). And there are no statistically significant differences in the average contributions of technological methods in improving the performance of the Palestinian government sector employees, by application to the Palestinian Ministry of Social Development, due to the gender variable. with the presence of statistically significant differences between the average contributions of technological methods in improving the performance of the Palestinian government sector employees, applied to the Palestinian Ministry of Social Development due to the variables (educational qualification, gender, years of experience, specialization, nature of the job) in the fields of availability of technological methods in the Ministry of Development Social, incentives for the use of technological methods in collecting and investing information in the ministry, the contributions of technological methods in improving the performance of Palestinian government sector employees, applied to the Palestinian Ministry of Social Development - Jenin Directorate, and the differences were in favor of bachelor’s holders. the study recommended: increasing the budget of the Ministry of Social Development for technological development and placing the development within the strategic plan of the ministry, training and empowering employees in the ministry to use technology methods, and increasing the number of human cadres in the ministry to reduce work pressure.